2005
DOI: 10.1096/fj.04-1970com
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase accelerates wound angiogenesis and wound healing in mouse and rat models

Abstract: Orchestration of the rapid formation and reorganization of new tissue observed in wound healing involves not only cells and polypeptides but also the extracellular matrix (ECM) microenvironment. The ability of heparan sulfate (HS) to interact with major components of the ECM suggests a key role for HS in maintaining the structural integrity of the ECM. Heparanase, an endoglycosidase-degrading HS in the ECM and cell surface, is involved in the enzymatic machinery that enables cellular invasion and release of HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
143
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 143 publications
(148 citation statements)
references
References 58 publications
5
143
0
Order By: Relevance
“…Applying a highly purified recombinant heparanase on the Qproteome GlycoArray, revealed high levels of N-linked mannose, in agreement with its high affinity to Concanavalin A lectin Zcharia et al, 2005), and low levels of bi-antennary structures and sialic acid (Table 1). Glycoanalysis obtained by the lectin array was confirmed by biochemical analysis (Table 1).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Applying a highly purified recombinant heparanase on the Qproteome GlycoArray, revealed high levels of N-linked mannose, in agreement with its high affinity to Concanavalin A lectin Zcharia et al, 2005), and low levels of bi-antennary structures and sialic acid (Table 1). Glycoanalysis obtained by the lectin array was confirmed by biochemical analysis (Table 1).…”
Section: Discussionsupporting
confidence: 56%
“…More recently, Verys et al have identified two additional cell surface receptors that mediate heparanase uptake, namely the low density lipoprotein receptor-related protein (LRP) and the mannose 6-phosphate receptor (MPR) as key elements in this process (Vreys et al, 2005), although a model that combine the three receptors has not been proposed. Heparanase has long been characterized as a glycoprotein and including Concanavalin A affinity chromatography in the purification scheme brought this feature into practice (Toyoshima and Nakajima, 1999;Zcharia et al, 2005). Six glycosylation sites were identified in the 50 kDa heparanase subunit (Hulett et al, 1999), and their role in protein secretion was established (Simizu et al, 2004), yet glycan biochemical analysis was not performed to date.…”
Section: Introductionmentioning
confidence: 99%
“…The remarkable heparanase-inhibitory activity of N-acetylated, glycol-split heparins together with the low levels of FGF-2 that they release from ECM and their inability to stimulate the mitogenic activity of FGF-2 indicates this class of chemically modified heparins as potential antiangiogenic and antimetastatic agents. These compounds also markedly inhibit wound angiogenesis in transgenic mice overexpressing the heparanase gene (65). Furthermore our preliminary experiments show that some of these heparin derivatives effectively abolish experimental lung colonization of intravenously administered B16-BL6 mouse melanoma cells (Ref.…”
Section: Figmentioning
confidence: 83%
“…Heparanase is overexpressed in myeloma cells 14 and in tissues after wounding. 15 Sdc1 with HS stubs rather than longer HSPGs is more susceptible to proteases that mediate shedding.…”
mentioning
confidence: 97%
“…Bacterial infections and sterile injuries induce the upregulation of sdc1, 4 heparanase, 15 and of proteases capable of cleaving sdc1 and releasing an ectodomain fragment. 48 The sdc1 ectodomain added to cells in culture suppressed the growth of tumor cells but had no impact on contact-inhibited cell lines.…”
mentioning
confidence: 99%